Maternal Factors as Determinants of Stunting in Children under the Age of Five: Scoping Review - Qoyimah, Anna Uswatun; Zahroh Shaluhiyah; Sri Winarni (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2024)
Background: Chronic malnutrition during a child's early years leads to stunting, a condition that can harm both their mental and physical development. Studies have indicated a correlation between parenting styles and stunted growth in children that the nutritional knowledge and practices of mothers significantly affect the dietary habits of toddlers. The perspectives and cultural convictions of mothers are significant but have received limited attention as factors that influence the nutritional well-being of children and adolescents. Aims: This review examined maternal factors as determinants of stunting in children under five. Methods: Three databases were used to search for literature, namely PubMed, Scopus, and Google Scholar. The key to the search is as follows: “maternal” or “mothers” and “factor” and “stunting” or “stunted” or “growth disorder” and “toddler” or “children under five.” The material displayed in search engines is selected based on inclusion and exclusion criteria. Result: This review was done on nine articles that were screened and analyzed out of 1,450 articles. The articles come from Nepal, India, Indonesia, Ghana, Congo, Uganda, Lebanon, and the Central African Republic. The type of research articles was cross-sectional and case-control. Conclusion: This review has provided an overview of maternal factors contributing to the prevalence of stunting. These factors include maternal employment, the educational status of mothers, maternal body mass index, the diversity of the mother-child diet, maternal exposure to mass media, and maternal age.